1998
DOI: 10.1111/j.1744-6570.1998.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Correlated Artifacts and True Validity on the Accuracy of Parameter Estimation in Validity Generalization

Abstract: The effect of non-zero intercorrelations among the three artifacts (criterion reliability, predictor reliability, and range restriction on the predictor) and true validity on the accuracy of estimation in two validity generalization models (Model 1 and Model 2) was investigated. Only the Thylor Series Approximation 1 (TSA1) procedure from Model 1 and the procedure with complete sample-based artifact data from Model 2 were included in this study. Six intercorrelation conditions (zero, low positive, medium posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Assumption 3). Raju et al (1998) showed that even if correlations do exist among the artifacts and r across studies, the accuracy of the estimation procedure derived from Model 2 was not affected.…”
Section: Model 2: Vg With Individually Corrected Correlationsmentioning
confidence: 95%
See 3 more Smart Citations
“…Assumption 3). Raju et al (1998) showed that even if correlations do exist among the artifacts and r across studies, the accuracy of the estimation procedure derived from Model 2 was not affected.…”
Section: Model 2: Vg With Individually Corrected Correlationsmentioning
confidence: 95%
“…James et al's descriptions of the hypothesized effects of situational moderators on the accuracy and/or the appropriateness of the current VG procedures are analytical in nature and thus require empirical verification. In a recent Monte Carlo study, Raju, Anselmi, Goodman, and Thomas (1998) have shown that if the third assumption is violated, then the estimates of the variance of r's derived from a procedure (TSA1) based on artifact distributions are not as accurate as the variance estimates based on a procedure that does not require this assumption; with respect to estimating the mean of r's, the TSA1 procedure performs better than the other procedure. It is important to note that in the Raju et al study, the violation of Assumption 3 that resulted in inaccurate estimates of V r was a correlation between r xy and the artifacts.…”
Section: Vg Models/proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important of these reasons is sampling error. The many VG studies and technical refinements of VG procedures that now exist in the literature in applied psychology (e.g., Aguinis, 2001;Aguinis & Whitehead, 1997;Hunter & Schmidt, 2004;Raju, Anselmi, Goodman, & Thomas, 1998;Schmidt & Hunter, 1998) suggest that VG is a robust phenomenon. Perhaps the most important implication of this work is that it has called attention to the fact that the mean of several validity coefficients may be a better …over the past several decades, there have been some significant advances in psychological science, specifically in our knowledge about important questions to address with respect to the development and use of assessment tools.…”
mentioning
confidence: 99%